2011
DOI: 10.1063/1.3646398
|View full text |Cite
|
Sign up to set email alerts
|

Kelvin probe study on formation of electric dipole at direct-contact HfO2/Si interfaces

Abstract: Although the direct-contact HfO2/Si structure has been demonstrated to have advantages on an equivalent oxide thickness scaling of <1 nm, characteristic electric charges have been reported to be formed at the HfO2/Si interface. A Kelvin probe method was used to examine the electric charges in HfO2/Si structures. We first describe the basic principles behind the Kelvin probe measurements of electric charges in an oxide/Si structure, and then point out what effect the surface adsorbates have on the measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
14
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 52 publications
3
14
0
Order By: Relevance
“…The surface carrier response should be taken into account for the semiconductor surface, but an n-type semiconductor surface can be analyzed like a metal surface provided that the response of holes can be neglected. The band diagram for the oxide/Si surface is quite similar to that obtained from MOS measurements except for the vacuum gap [43,44]. Thus, we can infer the distribution of electric charges inside the oxide/Si structure from the behavior of V CPD .…”
Section: Origin Of Interface Dipolesupporting
confidence: 61%
See 1 more Smart Citation
“…The surface carrier response should be taken into account for the semiconductor surface, but an n-type semiconductor surface can be analyzed like a metal surface provided that the response of holes can be neglected. The band diagram for the oxide/Si surface is quite similar to that obtained from MOS measurements except for the vacuum gap [43,44]. Thus, we can infer the distribution of electric charges inside the oxide/Si structure from the behavior of V CPD .…”
Section: Origin Of Interface Dipolesupporting
confidence: 61%
“…Thus, we can infer the distribution of electric charges inside the oxide/Si structure from the behavior of V CPD . Figure 5 plots the normalized CPD voltage ( δV CPD ) observed from the sample surface that includes both direct-contact HfO 2 /Si and HfO 2 /SiO 2 /Si stack structures, which indicates that the surface potential of the direct-contact HfO 2 /Si area is smaller by about 0.7 V than that of the HfO 2 /SiO 2 /Si stack area [ 44 , 45 ]. This potential difference is approximately consistent with the negative V fb shifts of MOS capacitors.…”
Section: Origin Of Interface Dipolementioning
confidence: 99%
“…However, the EWF controllability by the La-(Al) caps is lost when the SiO 2 IL is completely scavenged [ 49 ]. In addition, it was reported that complete elimination of IL from a SiO 2 /HfO 2 stack causes disappearance of the interface dipoles originating from Si-O-Hf bonds, resulting in disruptive shifts of V fb [ 50 ]. Therefore, leaving an ultra-thin SiO 2 IL after scavenging may be the key to avoid a disruptive change of EWF and to allow tuning by interface dipoles for CMOS integration using gate-first process.…”
Section: Interfacial Layer Scavenging Approachmentioning
confidence: 99%
“…As the simplest structure, we previously reported that a large dipole (>0.5 V) is formed at the HfO 2 /Si interface 28 , and proposed a bond polarity mechanism in which positive and negative alternating charged atoms produce a large potential difference between the HfO 2 and Si sides, as shown in Fig. 1a 29 , 30 . In this model, the polarizations of the interfacial Si-O and O-Hf bonds largely affect the total potential difference because these interface regions have small predicted local dielectric constants compared to Si and HfO 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Large interface dipoles are observed from the HfO 2 /Si structures, which are reasonably explained by the bond polarity mechanism, from ref. 29 . The IDM operation utilizes this mechanism.…”
Section: Introductionmentioning
confidence: 99%